Secure Information Flow for IoT Applications - Tri Minh Ngo; Nhat Vien Duy Nguyen (Society of Visual Informatics, 2019)
This paper discusses how to ensure security, i.e., confidentiality and integrity properties, for data in IoT applications. While confidentiality could be assessed via information flow analysis, integrity is ensured by error-correcting codes. In addition to errors, many communication channels also cause erasures, i.e., the demodulator cannot decide which symbol the received waveform represents. The paper proposes a method that might correct both errors and erasures together. Our method is efficient in reducing memory storage as well as decoding complexity.